PENERAPAN MODEL PEMBELAJARAN SCRAMBLE TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS VII SMP MUHAMMADIYAH BLIGO - Dewi Mardhiyana; Shochibul Izar (Delta: Jurnal Ilmiah Pendidikan Matematika, 2020)
The learning model is one of the keys to successful learning. The success of learning can be seen from the learning outcomes obtained by students, including the concept understanding ability. The concept understanding ability is the ability to express ideas in providing a picture, example, an idea or understanding, as well as a broader and creative explanation. This study aims to determine that the scramble learning model produces better conceptual understanding abilities than the direct learning model. This research design is a quasi experimental design, with the form of the nonequivalent posttest only control group design. The population in this study were all students of class VII SMP Muhammadiyah Bligo in the academic year 2019/2020. With cluster random sampling technique, selected 2 sample classes. The data collection method used the test. The data analysis method used proportion different test. Based on the calculation of the proportion difference test, the results obtained that z value of zcount = 2.016 and z0.05 = 1.64, so that zcount> z0.05 then H0 is rejected. This means that the scramble learning model results in student completeness in concept understanding abilities that is better than the direct learning model.